Arduino Uno based Vein detection design using High Power LED (HPL) - setiawan, Rizki; Mulya, Rudi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Difficulty in locating veins often poses a challenge in medical procedures such as intravenous catheterization or blood sampling, especially in children, adolescents, adults, and the elderly. This study designed and developed a vein detection device based on an Arduino Uno, utilizing a high-power LED (HPL) as the primary light source for locating veins. The device is equipped with a TTP223 touch sensor as the LED activation trigger and a PWM module to adjust light intensity according to the user's skin characteristics. The testing process was conducted on various age groups (children, adolescents, adults, and the elderly), with results showing that the device can clearly display veins, particularly in adolescents, adults, and the elderly, with optimal light intensity above 900 lux. The lowest average intensity was found in the children's group, indicating the need for more adaptive intensity adjustments. The device demonstrated stable and responsive performance and can assist medical personnel in accelerating the process of vein detection in a non-invasive, practical, and economical manner.